2017
DOI: 10.20964/2017.05.68
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sn Loading on the Characteristics of Pt Electrocatalysts Supported on Reduced Graphene Oxide for Application as Direct Ethanol Fuel Cell Anode

Abstract: The effect of Sn loading (5-30 mol %) on Pt catalysts supported on reduced graphene oxide was investigated for ethanol electro-oxidation in acidic medium. Reduced graphene oxide was synthesized via graphite oxidation-exfoliation process in liquid phase and chemical reduction. Pt and Pt x Sn y catalysts were deposited on reduced graphene oxide by a NaBH 4 impregnation-reduction method. The adopted procedures allowed the synthesis of graphene-like nanosheets where single Sn-doped Pt nanoparticles were impregnate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…On the other hand, GO with a lower concentration of functional groups shows a broad diffraction hump ranging from 15 • to 30 • , centered at 24.5 • , indicating a smaller interlayer distance between graphene sheets [20]. By applying Bragg's law, we determined that the interplanar spacing is 0.96 nm at 2θ = 9.1 • , a value similar to that reported in the literature [40]. For GO with a lower concentration of functional groups, the XRD pattern centered at 24.5 • has an interplanar spacing of 0.36 nm.…”
Section: Resultssupporting
confidence: 85%
“…On the other hand, GO with a lower concentration of functional groups shows a broad diffraction hump ranging from 15 • to 30 • , centered at 24.5 • , indicating a smaller interlayer distance between graphene sheets [20]. By applying Bragg's law, we determined that the interplanar spacing is 0.96 nm at 2θ = 9.1 • , a value similar to that reported in the literature [40]. For GO with a lower concentration of functional groups, the XRD pattern centered at 24.5 • has an interplanar spacing of 0.36 nm.…”
Section: Resultssupporting
confidence: 85%
“…Various catalytic methods are extensively being used to produce biofuel from biomass and inclusion of nanocatalysts can improve the product quality and its durability. It's the large surface area and rich catalytic action of nanoparticles that can help in dealing with the hurdles like inefficiency, fast deactivation-rate, time-consumption and mass-transfer resistance of heterogeneous catalysis [51,52]. In sequence of improving the effectiveness of fuel-cells, there is a need of a catalyst and Pt being a noble metal possesses good quality of catalyticefficiency.…”
Section: Role Of Nanotechnology In Biomass To Biofuel Conversion-nanomentioning
confidence: 99%
“…The second and recently explored type of research is the use of CBNs as supporting matrix which can act much less the same as the alloyed systems in terms of detoxification; or be combined with alloyed catalyst to further increase the electrocatalytic activities toward complete ethanol oxidation [ 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 ]. Goel and Basu reported a comparative study of CBNs-supported Pt–Ru and revealed that the maximum power density to be in the order Pt–Ru/MCN (mesoporous carbon nitride) > Pt–Ru/t-MWCNTs > Pt–Ru/MWCNTs > Pt–Ru/Vulcan-XC [ 84 ].…”
Section: Indirect Energy Conversion Challenges and Applications Ofmentioning
confidence: 99%
“…Instead of CNTs, graphene oxide was exploited and successfully applied as matrix to attach noble metals such as Pt and Pd [ 85 ]. Kumar et al reported a simple procedure to synthesize large-scale perforated graphene oxide nanosheets-Pd hybrids (Pd–FP–rGONSs) using microwave irradiation.…”
Section: Indirect Energy Conversion Challenges and Applications Ofmentioning
confidence: 99%